Evaluation of the safety and efficacy of topical mometasone furoate formulations - Chamboko, Bernadett Vongayi (Rhodes University, Faculty of Pharmacy, Pharmacy, 2007)
The human skin blanching assay (HSBA) is a well-researched and validated method for the bioequivalence assessment of topical corticosteroids. Traditionally, visual assessment of skin blanching has been used. Such testing methods are not conducive for interlaboratory comparisons. Regulatory bodies prefer less subjective methods of analysis. The FDA released guidelines on the assessment of bioequivalence for topical corticosteroids that recommends the use of a chromameter as a reliable method to measure skin blanching although the use of visual assessment with acceptable validation is also provided for. However, the FDA does not elucidate on the manipulation and handling of the chromameter during skin blanching measurements. The purpose of this project was several fold, which included investigations to standardize the manipulation and handling of a chromameter. In particular, measures to avoid skin whitening resulting from the effects of pressure on the skin during chromameter use were investigated. Other methods of analysis should surpass or at least be comparable to the HSBA if such methods are to be used for the assessment of topical corticosteroids. Microdialysis is a relatively new technique for assessing the rate at which drug penetrates the skin. The advantage of using this method is that there are fewer restrictions for selection of an appropriate study population unlike those required for the HSBA where one has to be both a 'responder' and a 'detector' for their results to be used in data analysis. Microdialysis was investigated by initially conducting experiments in which microdialysis probes were embedded into topical formulations containing mometasone furoate (MF) and the initial results revealed that relatively low drug was released from the formulations. These results indicated that should microdialysis be applied to measure the in vivo release of MF from such topical formulations following application to the skin, even lower concentrations of MF would likely result in the dialysate, necessitating the need for ultra-high sensitive methods of analysis. Typically, the availability of an appropriate analytical technique such as liquid chromatography coupled with mass spectrometry (LCMS) would be a pre-requisite for such in vivo studies. However, only high-pressure liquid chromatography (HPLC) and other less sensitive equipment was available in the laboratories. The study objectives were therefore focussed on in vitro assessment of the release of MF from topical formulations using microdialysis and Franz cells. In addition, the in vivo release of MF was also studied using the HSBA. Data obtained from the microdialysis experiments were compared with the data obtained from the Franz cell diffusion studies in order to provide information on the pharmaceutical availability of MF from the various topical MF dosage forms. Subsequently, pharmaceutical equivalence was investigated from the comparative pharmaceutical availability data using statistical analysis. An additional objective was to attempt to correlate in vitro with in vivo data (IVIVC) to establish a model that could be used to assess safety and efficacy of generic topical drug products. The in vivo data obtained from the HSBA were processed according to the FDA requirements and these pharmacodynamic data were subsequently compared with the microdialysis and Franz cell results. In summary the objectives of this project were: 1. To develop a system to improve the reproducibility of the use of a MinoltaÂ® chromameter and compare this with the standard/normal manipulation and handling of such instruments. 2. To develop and validate an HPLC method for the analysis of MF for use with in vitro diffusion studies using microdialysis and Franz cells. 3. To conduct a comparative HSBA on proprietary MF topical creams from two different countries in accordance with the FDA guidance. 4. To assess the pharmaceutical equivalence of topical formulations containing MF using Franz diffusion cells and in vitro microdialysis. 5. To compare the in vivo data obtained from the HSBA with those obtained in vitro using microdialysis and Franz cells.
Keywords: Adrenocortical hormones -- Physiological effect; Drugs -- Testing; Dermatopharmacology; High performance liquid chromatography